Clinical Findings in Patients Submitte to Cardiac Catheterization and Coronary Angiography at the Cardiovascular Center of Puerto Rico and the Caribbean: A Pilot Study - Pérez-Cardona, Cynthia M.; Guzmán-Serrano, Manuel; Cox-Rosario, Rafael A. (Puerto Rico Health Sciences Journal, 2014)
see manuscript